Applicability of dermoscopy for evaluation of patients' response to nonablative therapies for the treatment of superficial basal cell carcinoma. (1st April 2014) - Apalla, Z.; Lallas, A.; Tzellos, T.; Sidiropoulos, T.; Lefaki, I.; Trakatelli, M.; Sotiriou, E.; Lazaridou, E.; Evangelou, G.; Patsatsi, A.; Kyrgidis, A.; Stratigos, A.; et al.
Summary: Background: Applicability of dermoscopy in evaluation of outcome and monitoring of superficial basal cell carcinoma (sBCC) after nonablative therapies has not been sufficiently assessed. Objectives: Certain dermoscopic criteria, namely pigmented structures, ulceration and arborizing vessels, have been suggested to predict the presence of residual disease [residual disease‐associated dermoscopic criteria (RDADC)]. We aimed to assess this hypothesis. Patients and methods: Lesions exhibiting RDADC 3 months after treatment were biopsied and in the case of histopathological confirmation were excised. Lesions characterized by white/red structureless areas, superficial fine telangiectasias, or lacking any dermoscopic criterion, were monitored for 12 months. Results: At the 3‐month evaluation, one or more of the RDADC were detected in 25/98 (25·5%) sBCCs, in which histology confirmed tumour persistence. In 45 (61·6%) of the 73 remaining lesions, dermoscopy showed white/red structureless areas and/or superficial fine telangiectasias. Twenty‐eight lacked any dermoscopic criterion of sBCC. The two latter groups entered follow‐up. In total, disease recurred in 13 (17·8%) of the 73 lesions. Conclusions: RDADC accurately predict residual disease. Absence of dermoscopic criteria of sBCC safely predicts complete histopathological clearance. Detection of white/red structureless areas and/or superficial fine telangiectasias warrants close monitoring to recognize early recurrence.